Rosa1, a Transposable Element-Like Insertion, Produces Red Petal Coloration in Rose Through Altering RcMYB114 Transcription - Li, Maofu; Zhang, Hui; Yang, Yuan; Wang, Hua; Xue, Zhen; Fan, Youwei; Sun, Pei; Zhang, Hong; Zhang, Xinzhu; Jin, Wanmei (Frontiers in Plant Science, 2022)
Rose (Rosa sp.) flowers have a rich diversity of colors resulting from the differential accumulation of anthocyanins, flavonols, and carotenoids. However, the genetic and molecular determinants of the red-petal trait in roses remains poorly understood. Here we report that a transposable element-like insertion (Rosa1) into RcMYB114, a R2R3-MYB transcription factor’s promoter region causes its transcription, resulting in red petals. In red-petal varieties, RcMYB114 is expressed specifically in flower organs, but is absent from non-red varieties. Sequencing, yeast two-hybrid, transient transformation, and promoter activity assays of RcMYB114 independently confirmed the role of Rosa1 in altering RcMYB114’s transcription and downstream effects on flower color. Genetic and molecular evidence confirmed that the Rosa1 transposable element-like insertion, which is a previously unknown DNA transposable element, is different from those in other plants and is a reliable molecular marker to screen red-petal roses.